Implicit Attitudes and Road Safety Behaviors: The Helmet-Use Case - Ledesma, Ruben Daniel (2015)
We studied the role of implicit attitudes on road safety behaviors. We also explored the methodological benefits of using implicit measures to complement conventional self-reporting instruments. The results suggest that: (a) implicit attitudes are capable of predicting observed differences in the use of protective devices (helmet use); (b) implicit attitudes correlate with the emotional component of the explicit attitudes (e.g., perception of comfort?discomfort), but appear to be independent of the more cognitive components (e.g., perceived benefits); (c) the emotional component of the explicit attitudes appears to be the major predictor of behavior; and (d) implicit measures seem to be more robust against social desirability biases, while explicit measure are more sensitive to such bias. We conclude that indirect and automatic measures serve as an important complement to conventional direct measures (self-reports) because they provide information on psychological processes that are qualitatively different (implicit) and can also be more robust when it comes to response bias.